Jordan : Report on the Observance of Standards and Codes-Data Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
The report highlights the actions taken by the authorities to address the issues raised by the 2002 Data Report on the Observance of Standards and Codes (ROSC) mission for all macroeconomics statistics included in the ROSC exercise, namely national accounts, price, government finance, monetary, and balance-of-payments statistics. It also analyzes the authorities' plans for further improving the quality of the statistics, and reviews Jordan's current data dissemination practices against the requirements of the Special Data Dissemination Standard (SDDS).